Pengaruh Kualitas Produk, Harga, Dan Digital Marketing Terhadap Kepuasan Pelanggan Produk Ms Glow Di Jakarta - Umi Helfida Ali (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to examine the effect of price and product quality on purchasing decisions at MS Glow Beauty. The research object is a variable that is used as a research instrument, namely price (X1), product quality (X2) and purchasing decisions (Y). The population is MS Glow users who have tiktok social media of 294, and a sample of 28 people is taken. The sampling technique used is probability sampling, namely random MS Glow users who fill out the questionnaire. Data analysis techniques using descriptive analysis and verification. The results showed that price had a negative influence on purchasing decisions, product quality had a positive influence on purchasing decisions, price had no partial effect on purchasing decisions, quality had a partial effect on purchasing decisions and price and product quality simultaneously had an effect on purchasing decisions. Thus it can be concluded that price has no partial effect on MS.Glow consumer purchasing decisions, product quality has a partial effect on MS.Glow purchasing decisions, and price and product quality have a simultaneous effect on purchasing decisions.